Reversible Fluindione-Induced Chronic Interstitial Nephritis - Thomas Crepin; Jamal Bamoulid; Cécile Courivaud; Omar Dahmani; Sophie Felix; Didier Ducloux (Case Reports in Nephrology)
Fluindione is well known to induce acute drug-induced interstitial nephritis (IN). Most cases occurred soon after the onset of treatment. We report a unique case of severe subacute fluindione-induced IN diagnosed 2 years after the treatment was begun. Renal function dramatically improved after fluindione withdrawal and steroid therapy.